2017
DOI: 10.1128/aem.00459-17
|View full text |Cite
|
Sign up to set email alerts
|

PhaR, a Negative Regulator of PhaP, Modulates the Colonization of a Burkholderia Gut Symbiont in the Midgut of the Host Insect, Riptortus pedestris

Abstract: Five genes encoding PhaP family proteins and one phaR gene have been identified in the genome of Burkholderia symbiont strain RPE75. PhaP proteins function as the surface proteins of polyhydroxyalkanoate (PHA) granules, and the PhaR protein acts as a negative regulator of PhaP biosynthesis. Recently, we characterized one phaP gene to understand the molecular cross talk between Riptortus insects and Burkholderia gut symbionts. In this study, we constructed four other phaP gene-depleted mutants (ΔphaP1, ΔphaP2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…We first searched whether the five symbiont genomes carry the representative virulence or symbiosis factors previously reported in pathogenic species of BCC&P, such as B. pseudomallei ; plant growth-promoting rhizobacteria (PGPR) of PBE, such as B. phytofirmans ; and bean bug-associated SBE, such as B. insecticola [ 17 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We first searched whether the five symbiont genomes carry the representative virulence or symbiosis factors previously reported in pathogenic species of BCC&P, such as B. pseudomallei ; plant growth-promoting rhizobacteria (PGPR) of PBE, such as B. phytofirmans ; and bean bug-associated SBE, such as B. insecticola [ 17 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…We subsequently determined the complete genomes of two isolated symbionts of P. gutta and then compared them with the whole genomes of other three SBE symbionts. Studies on an SBE symbiont, B. insecticola RPE64, of the bean bug have revealed that several symbiosis factors, such as genes related to motility and cell wall synthesis, are important for colonization in the midgut crypts [17,[57][58][59][60][61][62][63][64][65][66]. The presence of all these symbiosis factors Figure 5B shows the comparison of COG functional categories between the above four classes of orthogroups, i.e., conserved in the seven species, conserved in only the five insect symbionts, conserved in only the two iPBE symbionts, and conserved in only the three SBE symbionts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have revealed part of the symbiont's mechanisms involved in these processes. The Burkholderia symbiont employs a unique corkscrew flagellar motility to pass through the constricted region (16); it undergoes cytological and metabolic alterations, such as flagella loss and polyhydroxyalkanoate accumulation, to cope with the crypt environment (17)(18)(19); and it rapidly proliferates to occupy entirely the available space in the lumen of the symbiotic M4 midgut region, notably by recycling host metabolic wastes into essential amino acids and B vitamins in the M4 crypts, which are thought to be part of the symbiont services provided to the host (17).…”
Section: Significancementioning
confidence: 99%